(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper explores the themes and narrative techniques in Louise Erdrich’s Tracks, focusing on the interwoven relationships between people, place, and identity. Erdrich’s works often challenge traditional narrative structures, using multiple narrators and non-linear storytelling to explore complex themes such as family, community, and cultural survival. In Tracks, she highlights the traumatic effects of colonization, particularly through the Chippewa experience, and examines how the destruction of traditional subsistence practices—like hunting and gathering—by Euro-American settlers undermined Indigenous kinship and environmental systems. The analysis adopts an ecocritical lens to show how Erdrich’s portrayal of nature reflects the Ojibwe worldview, where land is seen as a living, spiritual entity tied to cultural identity and survival. Through vivid metaphors and symbolic representations of nature, Erdrich critiques the ecological degradation caused by colonial capitalism and emphasizes the ongoing spiritual and cultural connections Indigenous people maintain with their ancestral lands. Ultimately, the paper underscores the significance of Indigenous ecological knowledge in fostering a more respectful relationship with the natural world, offering potential solutions to the contemporary environmental crisis.